The Non-linear Quantum Dynamics of Superconducting Circuitry - Morley, Grace (2023)
Over the last few decades, it has been established that the Josephson junction's (JJ) non-linear nature can be used to manufacture novel quantum Hamiltonians. The uneven spacing in the energy levels of circuits containing one or more Josephson junctions means that they can be thought of as forming something like an atom. These artificial atoms, when connected to one or more quantum harmonic oscillators formed by microwave cavities, can then be used to study the interaction of light and matter in a new field called circuit quantum electrodynamics (cQED).